만학도 간호대학생의 대학생활 경험 - 조영미(Young Mi Cho); 김은정(Eun-Jung Kim); 석소현(Soh Hune Sok) (한국콘텐츠학회 논문지, 19(2), 2019)
The purpose of this study is to deeply understand the college life experiences of older nursing students. We interviewed 7 older nursing students, and analyzed the data through Colaizzi's method which is one of the phenomenological research methods. There were 108 meaningful statements derived from the original data. It was composed of 20 themes, confirming the relationship with the original data. The 8 theme clusters and the five categories were organized. The five categories are: 'hardship of study', 'a solitary drifting ship', 'confront prejudice', 'weapons for only me', and 'a flower of hope'. As results of this study, it can be suggested that the development of an adaptive program for older nursing students. 본 연구의 목적은 만학도 간호대학생의 대학생활 경험을 깊이 이해하고자 수행되었다. 7명의 만학도 간호대학생을 눈덩이 방법을 통해 표집 하였고, 현상학적 방법 중의 하나인 Colaizzi의 방법을 통해 자료를 분석하였다. 분석결과 108개의 의미 있는 진술이 도출되었고, 8개의 주제모음과 5개의 범주가 확인되었다. 5개의 범주는 '고난 속 학업', '혼자 떠도는 조각배', '편견에 부딪힘', '나만의 무기', '그래도 희망은 꽃핌'으로 구성되었다. 본 연구의 결과는 만학도 간호대학생들을 위한 적응 프로그램의 개발과 주변의 의식전환 및 지지체계의 구축의 근거를 제시하는데 기여할 수 있으리라 사료된다.